"Healthier Than Just Healthy": Families Transmitting Health as Cultural Capital. (1st May 2020) - Mollborn, Stefanie; Rigles, Bethany; Pace, Jennifer A
Abstract: As the relationship between social class and health strengthens and socioeconomic and health inequalities widen, understanding how parents' socioeconomic advantage translates into health and class advantages in the next generation is increasingly important. Our analyses illustrate how a classed performance of "health" is a fundamental component of transmitting cultural capital in families and communities. Socially advantaged parents' health and class goals for children are often met simultaneously by building children's cultural capital in community-specific ways. This study uses observational, interview, and focus group data from families in two middle-class communities to illustrate how health-focused cultural capital acquisition plays out in everyday life. As parents manage children's lives to ensure future advantages, they often focus on health-related behaviors and performances as symbols of class-based distinction for their children. The synergy between family and community cultural capital is strengthening class and health advantages for some children, even as health-focused cultural capital often has drawbacks for stress and well-being. The intensification of and value placed on "health" in cultural capital may have long-term implications for health, socioeconomic attainment, and inequalities. If health-focused cultural capital continues to become increasingly salient for status attainment, its importance could grow, widening these gaps and reducing intergenerational mobility.